Combined effect of diabetes and frailty on mortality and incident disability in older Japanese adults. Issue 5 (20th February 2019) - Kitamura, Akihiko; Taniguchi, Yu; Seino, Satoshi; Yokoyama, Yuri; Amano, Hidenori; Fujiwara, Yoshinori; Shinkai, Shoji
Abstract : Aim: Evidence is limited on how frailty affects the association between diabetes and adverse outcomes at the population level. The present community‐based study aimed to clarify the relative risks of death and disability in older Japanese adults with diabetes, frailty, both or neither. Methods: The present prospective study analyzed data from 1271 Japanese residents aged ≥65 years in Kusatsu town in Gunma Prefecture, Japan, who participated in annual health checkups carried out between 2002 and 2011, and were initially free of disability. A Cox proportional hazards regression model was used to identify associations of diabetes and frailty with all‐cause mortality and incident disability. Results: Among the 1271 participants, 176 (14%) had diabetes (mean hemoglobin A1c 7.5%, body mass index 24.2 kg/m 2, 45% using diabetes medications) and 151 (12%) had frailty at baseline. Compared with non‐frail participants without diabetes, those with diabetes and frailty had higher risks of mortality (multivariable hazard ratio 5.0, 95% CI 2.4–10.3) and incident disability (hazard ratio 3.9, 95% CI 2.1–7.3). In contrast, non‐frail participants with diabetes did not have a significantly increased risk of mortality, although they had a higher tendency for the incidence of disability, as compared with non‐frail participants without diabetes. Conclusions: At the population level, the risks of death and disability in persons with mild diabetes were strongly affected by the presence of frailty. From a community‐based perspective, diabetes‐related mortality and disability incidence might be reduced by preventing or improving frailty in conjunction with glycemic control.Geriatr Gerontol Int 2019; 19: 423–428 .